2011
DOI: 10.5402/2011/719575
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Stenting in the Setting of Malignancy

Abstract: Esophageal cancer is often diagnosed at an advanced stage, with many patients found to have locoregional or metastatic disease at time of diagnosis. Because of this, cure may be unlikely, leading treatment efforts to focus more on symptom palliation and improving patient quality of life. The majority of patients with advanced disease suffer from some degree of dysphagia. Palliative efforts are therefore directed at relieving dysphagia, allowing patients to manage their oropharyngeal secretions, reduce aspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…Esophageal cancer often causes malignant esophageal stricture or even obstruction, which may lead to dysphagia and aphagosis, followed by severe malnutrition and malignant constitution [16]. These symptoms not only lower the quality of life tremendously in these patients, but the poor prognosis of esophageal cancer also means that surgical resection is not suitable for the majority of patients (>50%) because of poor patient condition.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer often causes malignant esophageal stricture or even obstruction, which may lead to dysphagia and aphagosis, followed by severe malnutrition and malignant constitution [16]. These symptoms not only lower the quality of life tremendously in these patients, but the poor prognosis of esophageal cancer also means that surgical resection is not suitable for the majority of patients (>50%) because of poor patient condition.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11]15 Our study has a stent re-insertion rate of 9%, which is at the lower end of the reported range of 7% to 26%. 6,9,13,14,16,17 Post-stent median survival is dismal, but unfortunately within the expected range for patients undergoing palliative treatment for oesophageal cancer. We believe this report demonstrates that good outcomes can be achieved with fluoroscopic-guided stent insertion by experienced radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is required to show whether covered or uncovered stents are preferable. 17,19 Our unit policy has been to use double layer stents, with an uncovered outer layer, as these have low displacement rates (0% in this series) and good technical outcomes, in terms of stent position and immediate postprocedure patency. 5 Thermal and ablative techniques, such as APC, have also been used but are not as widely available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, partially covered esophageal stents are preferred for palliation (3). But in the case of covered stents, 4-18% of cases experience tumor overgrowth at the ends of the stent (4). Docetaxel (DTX) is an anticancer drug used in the treatment of EC but systemic use of DTX is associated with neurotoxicity, musculoskeletal toxicity, and neutropenia.…”
Section: Introductionmentioning
confidence: 99%